THE EFFECT OF GENDER DIVERSITY, PROFITABILITY, LEVERAGE, AND FIRM SIZE ON RISK-TAKING IN BANKING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2019–2023 PERIOD - Ahmad Kodri Fauzi Hasibuan; Rizqi Husnul Khoiri; Andy Mulia; Siti Nurrahmawati; Novitasari Hasyim; Suci Indah Syafitri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the influence of Gender Diversity, Profitability, Leverage, and Firm Size on Risk-Taking in banking sector companies listed on the Indonesia Stock Exchange from 2019 - 2023. This research is associative, and the type of data used is secondary data obtained from financial statements and annual reports of companies published on the Indonesia Stock Exchange website (www.idx.co.id) and the respective companies' websites. The population of this study includes all banking sector companies listed on the Indonesia Stock Exchange from 2019 - 2023, totaling 39 companies. Based on predetermined criteria, the number of companies meeting the sample criteria is 27. The data analysis technique used is multiple linear regression analysis of panel data with a Fixed Effect Model approach. The results of the study indicate that Gender Diversity has a positive and significant effect on Risk-Taking, Profitability has a positive and insignificant effect on Risk Taking, Leverage has a positive and significant effect on Risk Taking, and Firm Size has a negative and significant effect on Risk-Taking.